Analisis Profil Konsumen Startup Ketringan dengan Pendekatan Desain Proposisi Nilai - Elsa Agustine Qamarani (Akademi Sekretari Manajemen Taruna Bakti, 2020)
Currently, Telkom University students have begun to build a startup, one of which is Ketringan. Ketringan is an application-based catering service and a site that connects restaurant vendors with customers. The phenomenon found in startup Ketringan is based on two services offered, namely Daily Catering and Events found considerable sales gap between the two services so that it is associated with the statement from the CEO of Ketringan that they have not served the University of Telkom students thoroughly. This research will reveal the needs and desires of customers by formulating the consumer profiles of Alexander Osterwalder and Yves Pigneur through the identification of customer jobs, pains, and gains. This research uses a qualitative method of descriptive with semi-structured interview data collection techniques, non-participant observation, and documentation. The results of the research and discussion are what consumers do, including ordering meals online, looking for catering information from friends. As for the things that are disturbing to the informant, such as prices are not comparable to the quality, the postage is expensive. Then, the consumer wishes to catering services that include variation of the menu, fast food delivery, review feature on the application, good communication with customers.